Nigeria Health Financing System Assessment - Hafez, Reem (World Bank, Washington, DC, 2018)
Nigeria's commitment to universal health coverage was enshrined by the passage of the National Health Act of 2014 in response to the continued underinvestment and poor performance of its health care system. Lack of data on available resources for health, the cost and use of health services, and the performance of front line providers has made it hard for the health sector to efficiently plan and advocate for additional investments in health. However, in the last 18 months, twoimportant sources of information were made available – the national health accounts (2010-2016) to look at resource allocation and spending decisions at the national level, and, a national health facility survey (2016) to assess the performance of service delivery at primary health care facilities. As such, while based on comprehensive analytics, this health financing system assessment was envisioned as a just-in-time policy brief on the health financing system that would provide actionable policy recommendations to the Ministries of Health, Budget and Planning, and the Vice President's office.